Pengaruh Green Perceived Quality dan Corporate Social Responsibility Terhadap Niat Beli Melalui Green Trust Sebagai Variabel Mediasi Produk Innisfree (Studi Kasus Pada Konsumen Pembeli Produk Innisfree di Wilayah Jabodetabek) - Pratiwi, Aulia; Ferry Wibowo, Setyo; Arvinta Monoarfa, Terrylina (PENG: Jurnal Ekonomi dan Manajemen, 2025)
In the increasingly tight competition in the beauty industry, companies need to understand the factors that can influence consumer purchasing decisions, especially related to environmental awareness. This study aims to analyze the effect of green perceived quality and corporate social responsibility on consumer purchase intentions, with green trust as a mediating variable, on Innisfree products in the Jabodetabek area. In this study, researchers used a quantitative approach involving 350 respondents who were consumers of Innisfree products. Researchers also used data analyzed by AMOS software version 24 and the SEM (Structural Equation Modeling) method. By producing research that shows that the influence of green perceived quality and corporate social responsibility has a positive and significant influence on purchase intentions, where green trust acts as a mediator that strengthens the relationship. However, in this case, the influence of the corporate social responsibility variable does not have a direct influence on purchase intentions through green trust as a mediator. These findings can provide important insights for companies to design more effective marketing strategies, while emphasizing the importance of commitment to sustainability and social responsibility in order to increase purchase intentions in consumers of Innisfree products.